Avseed Battery: Environmentally Friendly Battery Innovation as Electrolytes in Dry Batteries - Habibi, Rahmat Farhan; Dwiyanti, Alda; Suci Andarini, Annisa; Aji Putra Wibowo, Bayu; Harsono, Djiwo (P3M Politeknik Negeri Banjarmasin, 2024)
Energy is a fundamental force driving transformative processes across various domains. It is perpetual and adheres to the law of energy conservation, remaining indestructible. However, the challenge lies in the finite nature of conventional energy sources, which convert energy for intended purposes and cater to diverse needs, often escalating the overall cost. Among the commonly employed energy sources, batteries play a pivotal role. This study explores the viability of avocado seeds as potential electrolytes in dry batteries. The objectives are to assess the effectiveness of avocado seeds as electrolytes and to investigate the impact of solution concentration and composition on the generated electrical energy. A dry element battery, known for converting chemical energy into electrical energy through Redox (Reduction-Oxidation) electrochemical reactions, serves as the experimental focus. Using a quantitative approach with laboratory experiments, five treatments were administered, featuring different ratios (1:1, 1:2, 1:3), a negative control with avocado seeds, and a positive control with salt. The bio-battery effectiveness assessment revealed that the P4 composition (negative control with avocado seeds) exhibited the highest initial voltage of 3.4 V and an extended runtime of 156 hours. In summary, this research underscores the potential of avocado seeds as electrolytes in dry batteries, supported by observations of voltage levels and ignition times.